In the absence of an effective corporate bankruptcy system in China, how does the Chinese court use equal distribution in judgement executions to deliver fairness between competing creditors, 2017 - Zhang, Zinian (UK Data Service, 2022)
The interview data were collected by Dr Zinian Zhang from his fieldwork conducted in Hangzhou, the capital city of the Zhejiang Province, the People's Republic of China in May 2017. The interviews focused on the question of how the Chinese court conducts equal distribution in commercial judgment enforcements to deliver fairness between competing creditors. In total, there were sixteen law practitioners, including four judges and twelve lawyers, interviewed. Among twelve lawyers, nine once represented judgment creditors seeking equal distribution, and three represented clients who have to share. The data reveal that fair distribution is not as often used as thought, and that fair distribution is unable to fill the gap left by a corporate bankruptcy system. This application demonstrates that the quality of legal institutions can matter for economic development and that important policy lessons can be learned by China from the UK in this regard. This application recognises that China has been a remarkable economic success story but the country also faces new challenges as its economy enters a more mature phase. In particular, it needs to avoid the 'middle income trap' i.e. where a country has costs that are now too high to compete with low-income countries but where productivity does not match those in high-income countries. There are economies in Asia including Singapore and Hong Kong SAR that have emerged successfully from middle income status. Both these economies are built on UK law and are renowned for the quality of their legal infrastructure in supporting development of the financial system. The application suggests how China might also benefit from the UK experience in building its legal infrastructure. But the application recognises China's singular journey and avoids simplistic conclusions that certain consequences will inevitably follow form certain formal changes. It recognises the need for a continuous process of adaptation and development; learning appropriately from experience and responding sensitively to local conditions. The application demonstrates in particular how legal reforms can support economic growth through - enhancing the protections available to minority investors - supporting the availability of credit and contributing to lower-cost credit - supporting the restructuring of ailing businesses. n these areas we seek to provide options for enhancing and reforming the legal and financial system in China that are based upon the UK and other experience. We acknowledge that there are choices to be made between means and ends and that the relationship between means and ends is contingent and uncertain. The data we rely on will come principally from the World Bank Doing Business (DB) reports and rankings which are grounded on the notion that smarter business regulation promotes economic growth. The DB rankings have been issued annually since 2004 and the 2016 rankings includes 11 sets of indicators for 189 economies. Each economy is ranked on the individual indicators and also in an overall table. Currently, the UK is 6th in this table and China 84th but Singapore is 1st and Hong SAR is 5th which shows that it is possible for Asian economies to rank highly. In our project, we will explore deep into the detail underlying the Protecting Minority Investors, Getting credit and Resolving Insolvency indicators. These 3 indicators appear particularly pertinent to the development of a mature financial system and in relation to them all China ranks far below the UK. On protecting investors, China is ranked as 134th whereas the UK is 4th. We show how the gap can be bridged and how China can learn from the UK experience by examining critically how the UK has protected minority investors and ascertaining what measures of protection might work most effectively in Chinese conditions. Our approach takes the relevant DB rankings as a guide but subjects them to critical scrutiny and engaging systematically with the methodology underpinning the rankings; addressing the robustness of this methodology and considering alternative approaches. For instance, we will test the robustness and limitations of the DB 'resolving insolvency' data on China using Jiande Municipal People's Court in Zhejiang Province as a case study. This makes the process of data collection and analysis more manageable. 20 interviews with creditors and practitioners will be undertaken in Zhejiang Province and data on business closures from the local branches of the China Business Registration Authorities and the China Pension Management Authorities will also be collected. We will also use econometric analyses based on detailed micro data from other data sources.